Suaritinae new subfamily and Galeanites garcense new genus and new species of the Upper Jurassic Perisphinctaceae ammonites - Abelardo Cantú-Chapa (Revista Mexicana de Ciencias Geológicas)
Suaritinae new subfamily and Galeanites garcense new genus and new species represent a group of the Superfamily Perisphinctaceae (Ammonoidea, Cephalopoda) with pairs of ribs joined in ventrolateral tubercles. They are known from the Upper Jurassic (upper Tithonian) of Mexico, Cuba and Argentina… in order to continue, download the full paper in PDF.